Analyzing Social Media As The Most Effective Learning Media For Gen Z - Fajrinur; Novayanti, Sri; Bella, Ivvon Septina; Rahmati (LPPM Universitas Almuslim, 2024)
Currently, education in Indonesia has learnt and implemented many effective social media to achieve success in the teaching and learning process in the classroom. The current era is closely related to Generation Z children. Regardless of the pros and cons, almost every Generation Z student in Indonesia already has access to the internet and social media. So this research used library research in obtaining data on social media as the most effective learning media for Gen Z from articles, books, and previous researches. Research on social media advantages shows that it provides numerous benefits for students as long as it use responsibly. In fact, it can encourage students to learn collaboratively, enhance student interaction, enable students to develop critical thinking and boost their creativity. This is in accordance with the four competencies that students must have in the 21st century proposed by the Ministry of Education, called 4C, namely critical thinking and problem solving, creativity, communication skills, and ability to work collaboratively.